Upaya Pengenalan Gizi Seimbang Pada Anak Usia Dini Melalui Menu Hamburger Bergizi Di TK Walidah - M. Yusran Rahmat; Nur Ghina Aqilah; Supiana .; Roihanatus Salsabilla; Risma Wulandari; Rezti Suci Amelia; Adelia Putri; Nur Khalizah (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The golden age period is an important phase in forming healthy eating habits in early childhood. In Indonesia, the challenges that often arise are not just food availability, but low nutritional literacy and the tendency of children to reject vegetables due to taste preferences and the phenomenon of food neophobia. This research aims to describe the effectiveness of nutritious hamburgers as an innovative medium for introducing the concept of balanced nutrition to children aged 4-6 years at Walidah Kindergarten. The method used is descriptive qualitative involving students, teachers and parent representatives. Data was obtained through participatory observation during the manufacturing and consumption process, unstructured interviews, and field documentation, then analyzed using the Miles and Huberman model.Hamburgers are modified with high-fiber wheat bread, patties mixed with meat and chopped vegetables (carrots and spinach) as a camouflage technique, as well as vegetable toppings arranged to resemble interesting characters. The results show that children are more enthusiastic, especially when assembling their own food. Active involvement increases a sense of ownership, reduces resistance to vegetables, and makes it easier to understand nutrition through simple analogies. These findings confirm that modification of popular foods can be an effective strategy for balanced nutrition education and is worthy of being integrated into PAUD programs through collaboration between schools and parents. as well as further mixed-methods-based research to measure the sustainability of the long-term impact on stunting prevention and the formation of healthy eating behavior.